Determinants of Nurses' Preparedness for Disasters: A Cross-Sectional Study - Vanny Leutualy; Mevi Lilipory; Devita Madiuw; Dian Thiofany Sopacua; Fandro Armando Tasijawa; Valensya Yeslin Tomasoa; Joan Herly Herwawan; Feby Manuhutu; Lekdaina Kilikily (Fakultas Ilmu-ilmu Kesehatan, 2026)
It is essential to improve disaster preparedness of hospitals, as they are the front line of health care during natural disasters. Nurses have an important role in mitigating and handling the negative impacts of disasters. This study analyzes the determinants of nurses' preparedness for disasters. The researchers employed a quantitative, cross-sectional approach. Data was collected through the Disaster Preparedness Evaluation Tools (DPAT) questionnaire. Purposive sampling was used to select 265 respondents. The Spearman test results showed a weak, positive, and statistically significant relationship between knowledge and preparedness (r = 0.377, p = 0.000). Meanwhile, a strong positive and statistically significant relationship was found between role and preparedness (r = 0.615, p = 0.000). Conversely, the relationship between attitude and preparedness is not statistically significant (r = -0.044, p = 0.480). Next, the linear regression test shows that the most dominant factors, as indicated by the beta correlation coefficients, are role and knowledge: where an increase in one role score increases preparedness by 1.290 times, and an increase in one knowledge score increases preparedness by 0.300 times. Overall, this study shows that role and knowledge factors are positively related to nurse preparedness. Therefore, disaster simulations, training, and seminars must be conducted to enhance nurses’ preparedness and competence in disaster management.